A Comparison of Unilateral Deep Brain Stimulation (DBS), Simultaneous Bilateral DBS, and Staged Bilateral DBS Lead Accuracies. Issue 5 (28th March 2017) - Peng, Sophia; Levine, David; Ramirez‐Zamora, Adolfo; Chockalingam, Arun; Feustel, Paul J.; Durphy, Jennifer; Hanspal, Era; Novak, Peter; Pilitsis, Julie G.
Abstract : Background: Accuracy of lead placement within the brain can affect the outcome of deep brain stimulation (DBS) surgery. Whether performing unilateral lead implantation, simultaneous bilateral lead implantation, or staged bilateral lead implantation affects accuracy has not yet been assessed. We compare lead placement errors to evaluate whether one approach affords greater lead accuracy. Methods: We retrospectively reviewed 205 leads placed in 125 DBS surgeries. The accuracy of lead placement, defined by differences in x, y, and z coordinates and error vector magnitudes, was compared between three surgery groups: unilateral leads, bilateral leads placed simultaneously, and bilateral leads placed in staged surgeries. We also compared accuracies between first and second leads within each bilateral cohort and between second leads of the bilateral cohorts. Finally, we examined the effect of target and age on accuracy. Results: The accuracy of lead placement was comparable among unilateral, simultaneous bilateral, and staged bilateral leads. Timing of placement of the second lead in bilateral cases was not found to affect accuracy. The mean number of microelectrode trajectories was greater for first leads in simultaneous bilateral DBS ( p  = 0.032). No significant correlation between either age or target and accuracy was found. Conclusion: Although there may be other important reasons for performing DBS in a staged fashion, our study finds that neither laterality nor timing of second lead placement, patient age, or target site have significant impact on DBS lead accuracy, a finding that indicates with appropriate approach selection based on patient factors, accuracy does not have to be significantly compromised.